Competitive advantage from leveraging external resources : reuse of open source software components - Kurppa, Kimmo (2013)
This study is interested in how commercial firms can use open source software components and lines of open source software code as components in their own privately produced software products. International network of open source software (OSS) developers produces these reusable product components under permissive license conditions which allow firms to reuse the components and manufacture derivative works out of the reused components and then sell the derived works as a product at the market. Reusing readily developed and tested components, leveraging external resources, provides a competitive advantage for the firm using these components as resources in its software manufacturing. The competitive advantage derives from the nature of the resources in question. This study introduces that OSS components are self-renewing of their nature. The components renew regardless of the firm’s actions because the international network of OSS developers develop these resources voluntarily. When these works are released to public under a permissive license such as BSD license, the firm can use these works in its products for free, and also enjoy the free maintenance and updating of the components. This phenomenon induces welfare benefits for the economy and helps reducing Dead- Weight Loss, which is a result of classical blocking IPR’s. This study finds exceptional qualities in the OSS development phenomenon and therefore challenges the prerequisites of the Resource-Based View (RBV) theory once introduced by Barney (1991). The study ultimately finds that a starting software firm may enjoy competitive advantage as a result of its dynamic capabilities, as well as due to the special nature of the OSS components it uses as components in its products. The study introduces the view of Strategic Entrepreneurship and illustrates the process of developing competitive advantage and creating wealth. Key finding of the study is the special nature of open source software artifacts, which challenge the cornerstones of RBV theory. The study shows that the resource does not have to be rare, or in-imitable, or non-substitutable to produce competitive advantage for the firm.